Chaotic Dynamics and Chaos Control of Hassell-Type Recruitment Population Model - Guo Feng (Discrete Dynamics in Nature and Society)
For certain parameters, the mapping of a Hassell-type recruitment population model has a chaotic attractor. The control parameter is disturbed slightly with time by the improvement OGY method. When the mapping point wanders to the neighborhood of the periodic point, the control parameter is perturbed. The chaotic motion is controlled on the stable periodic period-1 point and period-2 orbits, and the influence of different control parameter ranges on the control average time is analyzed. When the selected regulator poles are different, the number of iterations used to control chaotic motion on a stable periodic orbit is different. Numerical simulations are presented to illustrate our results with the theoretical analysis and show the effect of the control method.